Comparison of green building research progress in China and south Korea: Trends and development 2001–2023 - Ren, Weicheng; Kim, Kyunghwan (Edelweiss Applied Science and Technology, 2025)
The development of green buildings is influenced by factors such as time, politics, society, economy, climate, and culture. China and South Korea share certain similarities in these areas and, since 2020, have both committed to specific carbon peaking and carbon neutrality goals. This study aims to compare green building research trends in China and South Korea, identifying key developments, differences, and shared challenges. It provides a brief overview of research progress in both countries since 2001 through a content review, followed by a comparative analysis across timelines and sub-dimensions, including technical, economic, legal, and systemic aspects. Additionally, a questionnaire survey was conducted with industry professionals in both countries to supplement the findings. The results indicate that while research directions are broadly similar, there are significant differences in specific topics and focus areas. Variations in timing and policy implementation also contribute to divergences in green building development. Moreover, both countries face common challenges that require further research and discussion. This analysis may offer valuable insights and references not only for China and South Korea but also for other developing nations.